Investigation on drilling response of Carbon-Graphene and Kevlar-Graphene composites. (2022) - Singh, D.; Kumar, R.R.; Gaur, P.; Rahul, D.; Jonathan Kiran, G.; Vijay, S.; Surya, S.; Jensin Joshua, J.; Subha, S.
Abstract: In this work, two sets of composites are fabricated - Carbon-graphene and Kevlar-graphene by hand lay-up method. The composites were drilled using four different drill bits with constant cutting speed of 1120 rpm and two different feed rates of 0.12 and 0.30 mm/s providing uneven damage outcomes. The drill damage area was assessed by enhanced radiography and using an image processing software GIMP, which helps in converting the radiographic images to binary images and assists in the reduction of noise from the resulting binary images. Using pixel area, we determine the damage area caused in each coupons and a comparative analysis is made between two different composites. Finally, the coupons are subjected to three experimental tests: 3point flexural (3 PB), 4-point flexural (4 PB), and Pin bearing. The Results obtained were correlated with the drilling-induced damage and mechanical resistance for both composites. The statistically tool was used to establish the model with relation between material resistance (3 PB and 4 PB) and the damaged area by drilling. In 3 PB flexural test, the flexural strength has not shown much variation with the damaged area. Alternatively, the 4 PB test, the flexural strength and in pin bearing test, the bearing strength decrease with increase in damage area. The brad drill tool appears to be more suited for drilling composite plates.